Photoelectrochemical cells employing molecular light-harvesting materials for the capture and conversion of solar energy - Kirner, Joel Thomas, author; Finke, Richard G., advisor; Reynolds, Melissa, committee member; Van Orden, Alan, committee member; Sampath, Walajabad, committee member (Colorado State University. Libraries, 2017)
Solar light has the potential to be a substantial contributor to global renewable energy production. The diffuse nature of solar energy requires that commercially viable devices used to capture, convert, and store that energy be inexpensive relative to other energy-producing technologies. Towards this end, photoelectrochemical cells have been the subject of study for several decades. Particularly interesting to chemists, molecular light-harvesting materials can be employed in photoelectrochemical cells. For example, a dye-sensitized solar cell (DSSC) is a type of photoelectrochemical cell designed to capture solar energy and convert it to electricity. Alternatively, molecular light-harvesting materials have also been employed in water-splitting photoelectrolysis cells (PECs), which capture solar energy and store it in the form of chemical bonds such as H2 and O2. The work presented in this dissertation falls into two major projects. The first involves fundamental studies of water-oxidizing PECs employing a novel perylene diimide molecule as the light-harvesting unit. Background is provided in Chapter II, composed of a comprehensive literature review of water-oxidizing PEC systems that employ light-harvesting materials composed of earth-abundant elements. Chapter III describes preliminary studies of a water oxidizing PEC composed of a perylene diimide organic thin-film (OTF) and cobalt oxide catalyst, the first of its kind in the literature. Characterization of this novel device provided knowledge of the efficiency-limiting processes that would need to be addressed in order to improve device performance. Subsequently, Chapter IV describes preliminary studies of the same perylene diimide molecule in an alternative, literature-precedented, dye-sensitized photoelectrolysis cell (DS-PEC) architecture aimed at improving the efficiency-limiting processes of the first OTF-PEC. Characterization of this DS-PEC architecture reveals that the efficiency-limiting processes of the OTF-PEC were indeed improved. However, deposition of the cobalt oxide catalyst onto the DS-PEC did not successfully result in water oxidation. Alternative catalyst-deposition strategies from the literature are described as direction for future studies. The second project of this dissertation involves the study of novel high-redox-potential organometallic cobalt complexes as redox mediators in DSSCs, and is presented in Chapter V. Therein, it was found that the use of electron-withdrawing functional groups on cobalt coordinating ligands not only increased the redox potential, but also increased the lability of the ligands. The resulting complex instability caused performance-limiting electron-recombination reactions in assembled DSSCs. These results point future researchers towards the study of higher-chelating ligands for enhanced stability in high-potential cobalt complexes.
Keywords: dye-sensitized solar cell; perylene diimide; water oxidation; organic thin-film; artificial photosynthesis; photoelectrochemical cell